Standards‐based modeling and deployment of serverless function orchestrations using BPMN and TOSCA. (27th January 2022) - Yussupov, Vladimir; Soldani, Jacopo; Breitenbücher, Uwe; Leymann, Frank
Abstract: Function‐as‐a‐Service (FaaS) is a cloud service model enabling to implement serverless applications for a variety of use cases. These range from scheduled calls of single functions to complex function orchestrations executed using orchestration services such as AWS step functions. However, since the available function orchestration technologies vary in functionalities, supported modeling languages, and APIs, modeling such function orchestrations and their deployment require significant technology‐specific expertise. Moreover, the resulting models are typically not portable due to provider‐ and technology‐specific details, and major efforts are required when exchanging an orchestrator or provider due to such lock‐ins. To tackle this issue, we introduce a vendor‐ and technology‐agnostic method for the modeling and deployment of serverless function orchestrations, which relies on the business process model and notation (BPMN) and topology and orchestration specification for cloud applications (TOSCA) standards for modeling function orchestrations and their deployment, respectively. We also present a toolchain for modeling serverless function orchestrations in BPMN, generating proprietary models supported by different function orchestration technologies from BPMN models, specifying their actual deployment in TOSCA, and then enacting such deployment. Finally, we illustrate a case study applying our method and toolchain in practice.